La responsabilidad compartida de los residuos posconsumo en el combate contra la contaminación transfronteriza - Efing, Antônio Carlos (2014)
This study analyzes the impact of the establishment of shared responsibility for post-consumer waste, as an instrument in the fight against environmental degradation, in the Brazilian legal system. it has as its premise that the increment of sustainability levels is essential, especially in the context of postmodernism, which is marked by mass consumption, extensive use of natural resources and the spreading of risks. Notably, consumer societies contribute enormously to the spread of this type of pollution, because they produce a profusion of consumer goods and, on the other hand, do not administer the post-consumer waste with the same efficiency. therefore, the proper management of product chain and life cycle waste is one of the greatest challenges to environmental preservation, especially in the case of the transportation of contaminants via natural forces, resulting in the so called transboundary pollution. the study found that only integrated actions among countries can lead to the preservation of an ecologically balanced environment to present and future generations. indeed, international cooperation is crucial to battle transboundary pollution, as well as to promote the establishment of legal systems which are compatible with the idea of sustainability. Furthermore, the study made it possible to conclude that shared responsibility, comprising introducing consumer’s active participation in reverse logistics, is fundamental to the achievement of the desired levels of sustainability. the present study was based on the deductive scientific method and predominantly relied on bibliographical resources.